MGNREGA: A Strong Pathway to Poverty Eradication: मनरेगा: निर्धनता उन्मूलन का सशक्त पाथवे - Singh, Vinay Kumar; Singh, Seema (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
To create employment opportunities in rural society, the Ministry of Rural Development, Government of India, launched an ambitious program in 2005 called NAREGA (renamed MGNREGA in 2009). Under MGNREGA, it is mandatory to provide 100 days of guaranteed wage employment per person per year, with a provision for 150 days in some special areas. Along with providing work, timely payment of wages is also mandatory, and in case of delay, compensation is provided. Unlike a welfare-based approach, MGNREGA is based on a rights-based approach, and it is recognized as the world’s largest employment guarantee program. MGNREGA has made a significant contribution toward poverty eradication, especially among marginalized groups like Scheduled Castes and Scheduled Tribes. Additionally, by reserving 33% of jobs for women, it has become a milestone in the journey of women empowerment. As a result, women now constitute nearly 50% of the workforce under MGNREGA. MGNREGA continues to set new milestones in preventing rural migration, environmental protection, providing equal employment opportunities, and developing rural infrastructure. The present research paper, titled "MGNREGA: A Strong Pathway to Poverty Eradication", studies the transformative impact of MGNREGA on rural society, particularly its role in eliminating rural poverty. However, along with these achievements, MGNREGA is also facing several serious challenges. The most significant is the financial crisis—evident from the budget cuts of 34% in 2021–22, 25% in 2022–23, and nearly 30% in the 2023–24 Union Budget. In addition to financial constraints, the scheme faces issues like bogus worker registrations, the rise of a NREGA mafia, inefficiencies in the financial delivery mechanism, and administrative apathy. To overcome these challenges, the Government of India is continually making efforts to improve MGNREGA through new innovations and operational guidelines. After nearly two decades of implementation, MGNREGA is widely regarded as a successful program for rural transformation and poverty alleviation. In this context, the World Bank has also recognized MGNREGA as a "strong social security" instrument for rural development. Abstract in Hindi Language: ग्रामीण समाज में रोजगार के अवसर उपलब्ध कराने हेतु ग्रामीण विकास मंत्रालय, भारत सरकार द्वारा 2005 में NAREGA (2009 में MGNREGA) जैसा महत्वाकांक्षी कार्यक्रम प्रारंभ किया गया। मनरेगा द्वारा प्रति व्यक्ति प्रतिवर्ष 100 दिन का विधिक कार्य देना अनिवार्य है, कुछ विशेष स्थान पर यह व्यवस्था 150 दिनों की है। कार्य देने के साथ निश्चित समयावधि में उनका भुगतान अनिवार्य रूप से किया जाना है अन्यथा की स्थिति में क्षतिपुर्ति की भी व्यवस्था है। ‘कल्याण आधारित दृष्टिकोण‘ के स्थान पर ‘‘अधिकार आधारित दृष्टिकोण‘‘ पर आधारित मनरेगा सर्वाधिक रोजगार देने वाला विश्व का सबसे बड़ा कार्यक्रम है। मनरेगा द्वारा वंचित वर्गों विशेष कर अनुसूचित जाति एवं जनजातियों में निर्धनता उन्मूलन का सफल प्रयास किया गया है। साथ ही महिलाओं को 33% कामगार आरक्षण देकर महिला सशक्तिकरण की दिशा में भी मील का पत्थर साबित हुआ है, परिणामतः मनरेगा में महिला कामगारों का वर्तमान अनुपात लगभग 50% के आसपास है। ग्रामीण प्रवास को रोकने, पर्यावरण संरक्षण, रोजगार के समान अवसर उपलब्ध कराने, ग्रामीण इंफ्रास्ट्रक्चर के विकास आदि में मनरेगा नित नए आयाम स्थापित करते जा रहा है। प्रस्तुत शोध पत्र ‘मनरेगा: निर्धनता उन्मूलन का सशक्त पाथवे‘ में मनरेगा द्वारा किये गए ग्रामीण समाज का रूपांतरण विशेष कर ग्रामीण निर्धनता उन्मूलन संबंधी अध्ययन किया गया है। मनरेगा उक्त उपलब्धियों को स्थापित करने के साथ कई गंभीर चुनौतियों का सामना कर रहा है। इसमें सबसे प्रमुख चुनौती वित्तीय संकट की है, जिसके अंतर्गत 2021.22 में 34% 2022.23 में 25% तथा 2023.24 के बजट में लगभग 30% के आसपास बजटीय कटौती दिखाई पड़ती है। वित्तीय चुनौती के साथ मनरेगा बोगस वर्कर रजिस्ट्रेशन, नरेगा माफिया, वित्तीय डिलीवरी मैकनिज्म, प्रशासनिक उदासीनता जैसी अनेकानेक चुनौतियों का सामना कर रहा है। उक्त चुनौतियों के समाधान के लिए भारत सरकार दिन प्रतिदिन नए नवाचार एवं गाइडलाइन द्वारा मनरेगा को उपयोगी बनाने का सफल प्रयास कर रही है। लगभग दो दशक की यात्रा के पश्चात् मनरेगा को ग्रामीण रूपांतरण, ग्रामीण निर्धनता उन्मूलन का एक सफल कार्यक्रम माना जाता है। इसी संदर्भ में World Bank द्वारा इसे ग्रामीण विकास का ‘‘मजबूत सोशल सिक्योरिटी‘‘ माना गया। Keywords: मनरेगा, काम का अधिकार, न्यूनतम मजदूरी दर, e-fms (electronic fund management system), ग्रामीण रूपांतरण, ग्रामीण प्रवास, ऑपरेशनल गाइडलाइंस।